Odontogenic carcinosarcoma: a comprehensive review of clinical and therapeutic insights - Muhammad Osama; Cyril Kocherry; Farid Ullah; Safiyyah Ubaid; Maryam Ubaid; Ubaid Ullah; Aishah Binte Nawaz; Hanan M. Qasem; Ramez M. Odat; Muzammil Farhan; Raheel Ahmed (Frontiers in Oral Health)
Malignant odontogenic tumors are rare, accounting for only 1%–6.1% of all odontogenic tumors. Among them, odontogenic carcinosarcoma (OCS) is an exceptionally rare and aggressive malignant neoplasm originating from dental tissues. First recognized by the World Health Organization (WHO) in 1992, OCS is characterized by high-grade biphasic malignant epithelial and mesenchymal components, contributing to its aggressive clinical behavior. OCS often presents with nonspecific symptoms such as pain, swelling, and loosening of teeth, which complicate early diagnosis. Its rarity adds to the diagnostic challenges, frequently leading to delays in identification. Histopathological evaluation remains the cornerstone for accurate diagnosis, distinguishing OCS from other odontogenic tumors through features like epithelial nuclear pleomorphism, mitotic activity, and mesenchymal sarcomatous differentiation. Management typically involves surgical resection with clear margins, while adjuvant therapies such as chemotherapy and radiation are considered in select cases. Recent advancements in molecular oncology and surgical techniques, including robotic-assisted procedures and 3D-printed reconstructive aids, offer promising avenues for improving patient outcomes. A multidisciplinary approach and ongoing research are essential to enhance diagnostic accuracy, refine treatment protocols, and improve the prognosis for patients affected by this rare malignancy. The primary objective of this review is to consolidate current knowledge on OCS, focusing on its diagnostic complexities, treatment strategies, and potential emerging therapies.